Micro credit as a tool for poverty reduction : changes in economic activities of poor households and their socio-economic and spatial impacts a case study of Pagadian City Zamboanga del Sur, Philippines - Rawal, Vikas (2007)
Micro-credit has become on eof the popular development instruments since its wide success in Bangladesh. In the past, the Government of the Philippines has enhanced on a similar policy since independence in the 1940s. The policy however, seems to focus more on the aspect of credit coverage rather than on its impact on households, the community and land use. Unlike all previous studies on micro-credit, the present study focuses on impact of micro-credit on different household characteristics and its effects on the community and land use. This is done in order to find out what difference micro-credit can bring to poor households who avail of micro-credit and how their utilization of their small loans can result in changes on land use. The principal aim of the study was to identify the changes in income, employment, access to health and education facilities, and spatial impact due to use of micro-credit. The study further looked into the reasons for failure of the micro-credit programs. The study found out that the employment and income level of poor households increased after they used micro-credit and they were able to create new assets. Increased income enabled poor households to access health and education facilities more easily. It was also found that micro-credit allowed farming households to intensify and expand farming activities. Moreover, borrowing households were able to rent or lease additional land for farming purposes. On the other hand, the study has identified some households who could not repay their credit because they either used their credit to repay loans from other sources or used it to buy immediate needs. The study recommends that micro-credit be utilized for intensifying utilization of idle lands. The use of micro-credit to rent or lease land may also be promoted as an alternative tenure type that addresses the problem of landlessness. It also recommends that micro-credit programs should be designed according to the household and local socio-economic characteristics of target clientele.